PENERAPAN METODE THINK PAIR SHARE DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INDONESIA KELAS VI SD NEGERI 168060 TEBING TINGGI - Nedi Kristina Simamora (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This aim of this research is to improve learning result on Indonesian langauge subject  through think pair share method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SD N 168060 Tebing Tinggi which amounted to 35 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the think pair share method of Indonesian language subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (68,57%), the first cycle (77,14%), cycle II (91,42 %) and complete learn the clasical equal to 91,42 %.Keywords : Think-Pair-Share, Indonesian Language, Learning Result